Factors associated with therapeutic response in acromegaly diagnosed in the elderly in Spain - Biagetti, Betina; Iglesias, Pedro; Villar-Taibo, Rocío; Moure, María-Dolores; Paja, Miguel; Araujo-Castro, Marta; Ares, Jessica; Álvarez-Escola, Cristina; Vicente, Almudena; Álvarez Guivernau, Èlia; Novoa-Testa, Iria; Guerrero Perez, Fernando; et al. (Frontiers in Endocrinology, 2022)
Abstract Context: Some reports suggest that acromegaly in elderly patients has a more benign clinical behavior and could have a better response to first-generation long-acting somatostatin receptor ligands (SRL). However, there is no specific therapeutic protocol for this special subgroup of patients. Objective: Study aimed at identifying predictors of response to SRL in elderly patients Design: Multicentric retrospective nation-wide study of patients diagnosed with acromegaly at or over the age of 65 years old. Results: One-hundred and eighteen patients (34 men, 84 women, mean age at diagnosis 71.7 ± 5.4 years old) were included. Basal insulin-like growth factor type 1 (IGF-1) above the upper limit of normal (ULN) and growth hormone (GH) levels (mean ± SD) were 2.7±1.4 and 11.0±11.9 ng/mL respectively. Mean maximal tumor diameter was 12.3 ± 6.4mm and up to 68.6% were macroadenoma. Seventy two out of 118 patients (61.0%) underwent surgery as primary treatment. One third of patients required first-line medical treatment due to a rejection of surgical treatment or non-suitability because of high surgical risk. After first-line surgery 45/72 (63.9%) were in disease remission, and 16/34 (46.7%) of those treated with SRL had controlled disease. Patients with basal GH at diagnosis ≤ 6 ng/mL had lower IGF-1 levels, had smaller tumors and more patients in this group reached control with SRL (72.7% vs 33.3%; p<0.04) [OR: 21.3, IC: 95% (2.4 -91.1)], while male patients had a worse response [OR: 0.09, IC 95% ( 0.01- 0.75)]. The predictive model curve obtained for SRL response showed an AUC of 0.82 CI (0.71–0.94). Conclusions: The most frequent phenotype in newly diagnosed acromegaly in the elderly includes small adenomas and moderately high IGF-1 levels. GH at diagnosis ≤ 6ng/ml, female gender, but not the age per se, were associated with a greater chance of response to SRL.